2000
DOI: 10.2460/ajvr.2000.61.816
|View full text |Cite
|
Sign up to set email alerts
|

Failure to detect bovine immunodeficiency virus contamination of stud bull spermatozoa, blood leukocytes, or semen leukocytes in samples supplied by artificial insemination centers

Abstract: Contrary to our report of high point prevalence of BIV contamination of semen from a single artificial insemination center, bulls of the study reported here did not appear to be infected. Maximum risk of BIV infection in similar bulls was estimated at 10% with a confidence level of 95%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…28 In a survey of 30 BIV-seronegative bulls at 3 artificial insemination centers, there were no BIV-positive bulls detected by use of PCR analysis of semen leukocytes, spermatozoa, or blood leukocytes. 29 There is limited evidence to support vertical transmission. It was reported that 40% (14/35) of naturally infected BIV-seropositive cows gave birth to BIV-seropositive calves, 30 and calf BIV antibody status before ingestion of colostrum was not associated with development or frequency of clinical signs.…”
Section: Host Range and Transmissionmentioning
confidence: 98%
“…28 In a survey of 30 BIV-seronegative bulls at 3 artificial insemination centers, there were no BIV-positive bulls detected by use of PCR analysis of semen leukocytes, spermatozoa, or blood leukocytes. 29 There is limited evidence to support vertical transmission. It was reported that 40% (14/35) of naturally infected BIV-seropositive cows gave birth to BIV-seropositive calves, 30 and calf BIV antibody status before ingestion of colostrum was not associated with development or frequency of clinical signs.…”
Section: Host Range and Transmissionmentioning
confidence: 98%
“…For several virus types, it has been shown that most virus particles are free in the seminal plasma instead of penetrating or attaching to spermatozoa. [17][18][19] Taking both CCMV analysis techniques into account, the CCMV removal is at least 84±4%. Similar to other virus removal techniques from semen 21,22 , not a complete virus elimination was achieved.…”
Section: Lab On a Chip Accepted Manuscriptmentioning
confidence: 99%
“…Most of the viruses can be found free in the seminal plasma or in somatic cellular components and not in the spermatozoa fraction. [17][18][19][20] With the implementation of a virus removal processing step during daily AI laboratory procedure, the viral load and therewith the risk of disease transmission is decreased. Since the chance of disease transmission is related to the viral load, lowering this will facilitate safer insemination with fresh semen, which is currently used for AI of sows.…”
Section: Introductionmentioning
confidence: 99%